Organizational Identity for Cross-border Digital Trade: Achieving Technical and Legal Interoperability Within the Model Law on the Use and Cross-border Recognition of Identity Management and Trust Services (MLIT) Using the vLEI - Marin, Ivan; Castellani, Luca G. (United Nations Commission on International Trade, 2025)
Identity management is a cornerstone of digital trade and a core component of trust services, starting with electronic signatures. However, there is limited awareness of its legal and technical implications. The United Nations Commission on International Trade Law (UNCITRAL) has prepared a Model Law on the Use and Cross-border Recognition of Identity Management and Trust Services to provide uniform guidance on how to establish an enabling legal environment for identity management and trust services. The Global Legal Entity Identifier Foundation (GLEIF) has developed the Legal Entity Identifier (LEI) and its digital counterpart the verifiable LEI (vLEI) as universal solutions for a secure and cost-effective persistent business identifier. This paper illustrates how the MLIT and the vLEI may interact to provide legal and operational certainty to identification needs, thus fostering global economic growth.
Keywords: Digital cross-border trade; Digital trade; GLEIF; LEI; Legal entity digital identity; MLTR compliance; Trade facilitation; vLEI verifiable credential

The Middle Eastern and African Arbitration Review 2025 : Telecoms disputes in the Middle East and Africa - Mouzoula, Natalia; Kamau, Alice (Anjarwalla Collins & Haidermota, 2025)

The Middle Eastern and African Arbitration Review 2024 : CRCICA and new CRCICA Arbitration Rules - Selim, Ismail; Hafez, Mohamed (The Cairo Regional Centre for International Commercial Arbitration, 2024)

The International Tax Regime Complex: Understanding Change in Global Tax Governance - Kuhn, Katharina; Cadzow, Lucinda; Heitmüller, Frederik; Hearson, Martin; Randriamanalina, Tovony (Institute of Development Studies, 2024)
Keywords: Global tax governance; International tax; Legitimacy; Low-income countries; Regime complex; UN Framework Convention on International Tax Cooperation

Digitization and sustainability: Practical convergences of two leading discussions in business law - Mittwoch, Anne-Christin (Beiträge zum Transnationalen Wirtschaftsrecht, 2024)
Until now, digitization and sustainability have stood side by side in the discussion of business law. As leading discourses of the present-day business scene, both topics are leading to profound change in companies and are influencing each other in the process - a circumstance that can no longer be ignored by corporate management. The article shows the guiding ideas behind both discussions, as well as their convergences and interactions, and asks about the effects they have on management's duty to act.
Keywords: Corporate Digital Responsibility; Corporate Sustainability; Digitization; Directors' Duties; Sustainability

Assessment Report of Arbitration Centre in Egypt (CRCICA) - SNFI (African Development Bank, 2022)

COFOLA International 2022: Current Challenges of Resolution of International (Cross-Border) Disputes - Drličková, Klára; Malachta, Radovan; Provazník, Patrik (Masaryk University Press, 2022)
- Bridging the Public-Private Law Divide in the Conflict of Laws; - New Practices in Alternative Dispute Resolution: New Pathways to Peace; - The Singapore Convention: A Giant Leap for Mediation or Just Too Good to Be True; - Potential Nexus Between the Enforceability of Foreign Judgments and the Quality of Civil Justice in ASEAN Did the Preliminary Objections Judgment Resolve the Chagos Archipelago Sovereignty Dispute? - The Order of Periodic Penalty Payments by the CJEU in Cases Filed by a State Against Another State; - The Dichotomy of Obligations of Conduct and Result in International Investment Law; - Investment Arbitration Reform: Third-Party Funding in Investment Arbitration; - Between Protection and Access to Justice: On the Regulation of Returns in Third-Party Litigation Funding; - Contract Adjustment in Arbitration : Should the Approach Be Adjusted? - Current Challenges of Enforcing Annulled Arbitral Awards; - Condifentiality of Arbitral Awards on National, International and Institutional Level; - Digitalisation of Judicial Cooperation in the EU: A Long Road Ahead; - Resolving Cross-Border Consumer Disputes: The Digital Experience in China; - Law Applicable to Non-Consumer Contracts Concluded at an Electronic Auction; - Can Robot Judges Solve the So-Called “Hard Cases”? - Current Challenges of Cross-Border Disputes in Slovakia : Is Slovak Law Anchored in the 21st century

COFOLA International 2021: International and National Arbitration: Challenges and Trends of the Present and Future - Malachta, Radovan; Provazník, Patrik (Masaryk University Press, 2021)
- Virtual Arbitration Hearings in Times of COVID-19 (And Beyond); - International Arbitration and Blockchain: Current State, Types, Characteristics and the Future Perspective; - Use of Artificial Intelligence in Arbitration; - The Impact of Brexit on the Arbitration Procedure in Great Britain; - May Misapplication of EU Law Give Rise to International Responsibility of the Member State ... Under Investment Treaties? - International Investment Court System: The Future of Investment Dispute Settlement? - EU and Its New Mechanism for the ISDS in the Protection of FDI – What the Future Holds? - (Un)Clean Hands in International Investment Arbitration: Some Cleaning Required? - Challenges of Arbitrators in Inter-State Cases: A Different Cattle of Fish? - “Rules of Law” and Lex Mercatoria Determination Under the Auspice of ICC Arbitration; - Sources of Transnational Public Policy in International Commercial Arbitration; - Regulation of Arbitration Agreements Under New York Convention; - Comfortable Satisfaction Before the Court of Arbitration for Sport: Consistency Despite Differences? - Comparison of ICC Expert Report vs. ICC Arbitration Award; - Analysis of Civil Law Consequences of Corruption Under the Czech Law... in the Light of International Commercial Arbitration; - The Crime of Bending the Law From the Point of View of the Arbitrator ... of the Court of Arbitration and Application Practice; - The Arbitration Convention as One of the Measures to Eliminate Double Taxation ... in the European Union and in Slovak Republic; - Possibility of Resolving Individual Labor Disputes in Croatian Law by Arbitration; - What We Know, We Don’t Know About Macao’s Arbitration Framework and the Way Forward.

Fiscal Potential and Political and Institutional Constraints to Increasing Domestic Revenues - Niang, Birahim Bouna; Mbaye, Ahmadou Aly (Center for Global Development, 2020)

How Countries Can Fully Implement the New York Convention: A Critical Tool for Enforcement of International Arbitration Decisions - Forneris, Xavier; Mocheva, Nina (Washington DC, 2019)
The year 2018 marked the 60th anniversary of the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards, the most important international convention in the area of international commercial arbitration. The Convention is also said to be the most successful international treaty in the area of private international law. This note primarily targets policy makers and their legal advisors in countries looking at ways to improve their business environment, to become more attractive locations for trade and investment, through better dispute resolution options for international transactions. First, the note explains that international commercial arbitration, as part of countries' legally recognized dispute resolution options, is critical to cross-border contract enforcement. As countries strengthen their international arbitration regimes, they improve their competitiveness in international markets and increase investment and trade by reducing transaction risks and the cost of new infrastructure projects. Countries can improve their international commercial arbitration systems by passing modern legislation consistent with international best practice, ratifying international arbitration conventions, strengthening judicial capacity to enforce arbitral awards, and investing in local arbitration centers.

COFOLA International 2019: Private Enforcement of Antitrust Law and Unfair Competition with Cross-border Element - Drličková, Klára (Masaryk University Press, 2019)
Constitutional Questions about the Directive on Antitrust Damages Action ... : The Rule of Binding Effect of National Competition Authorities’ Decisions Arbitrability of the EU Antitrust Law Consumer Decision Making Process as a Centre of the Marketplace Effects Rule
Keywords: Actes de conférence; Competition law; Concorrência desleal; Concurrence (droit); Concurrence déloyale; Droit de la concurrence; E-knihy; Knihy; Litiges internationaux; Mezinárodní spory; Nekalá soutěž; Právo; Právo hospodářské soutěže; Sborníky konferencí; Čítárna

Financing Infrastructure in Africa - Ashiagbor, David; Deiana, Rodrigo; Kappeler, Andreas; Minsat, Arthur; Nguyen-Quoc, Thang; Bank, European Investment (European Investment Bank, 2018)

The Banking Sector in the Central African Economic and Monetary Community (CEMAC): Great Potential in the Face of Enormous Challenges - Benhamdane, Jad; Hidane, Said; Stijns, Jean-Philippe; Bank, European Investment (European Investment Bank, 2018)

First Brno Arbitration Conference 2017: Current Issues of International Commercial Arbitration - Drličková, Klára; Halla, Slavomír (Masaryk University Press, 2017)
Content research papers : - The Application of CISG in International Arbitration; - CISG and Arbitration in the Hungarian Legal Practice; - Time Limits in Arbitration Agreements : What Can We Expect, if We Fail to Meet Them? - Interpretation Hardships Regarding the CISG, in Particular Article 7; - Awarding Punitive Damages in Czech Arbitration Proceedings; - Award of Legal Costs in Arbitration with Focus on Regulation in the Slovak Republic; - Advantage or a Disadvantage? The Costs of Arbitration Court Proceedings in Hungary.

Assessment Report of Arbitration Centres in Côte D’ivoire, Egypt and Mauritius - ORPF (African Development Bank, 2014)

Arbitrating and Mediating Disputes: Benchmarking Arbitration and Mediation Regimes for Commercial Disputes Related to Foreign Direct Investment - Pouget, Sophie (World Bank, 2013)
An effective commercial arbitration regime matters for foreign investors. It gives parties the autonomy to create a dispute resolution system tailored to increasingly complex disputes. Foreign investors view arbitration as a way to mitigate risks by providing legal certainty on enforcement rights, due process, and access to justice. The Arbitrating and Mediating Disputes indicators assess the legal and institutional framework for commercial arbitration, mediation, and conciliation regimes in 100 economies. All surveyed economies recognize arbitration as a tool for resolving commercial disputes and only nine economies have not acceded to the New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards. In the Arbitrating and Mediating Disputes indicators, High Income OECD and Eastern Europe and Central Asia are the regions that reformed their laws on alternative dispute resolution the most between 2011 and 2012. The data also show that, globally, arbitration proceedings take 326 days on average, while recognition and enforcement proceedings of foreign arbitral awards take 557 days on average. The Arbitration and Mediating Disputes indicators are significantly correlated with perception data on the importance of alternative dispute resolution, as well as other measures such as total foreign direct investment inflows and inflows per capita, the Doing Business 2013 Enforcing Contracts data, the World Bank Group's Governance Indicators, the World Economic Forum's Global Competitiveness Indicators, and the Multilateral Investment Guarantee Agency's World Investment and Political Risk data. The paper concludes by identifying several opportunities for improvement, such as greater flexibility for domestic arbitration regimes, faster arbitration proceedings, and better domestic court capabilities.

Trade agreements and bilateral trade in sub-Saharan Africa: Estimating the trade effects of the EU-ACP PTA and RTAs - Turkson, Festus Ebo (CREDIT Research Paper, 2012)
This paper on Trade Agreements within SSA, is an assessment of the ex post bilateral trade effect of the European Union-African Caribbean Pacific Preferential Trade Agreement (EU-ACP PTA) and sub-regional regional trade agreements (RTAs) on bilateral trade involving SSA countries. The main objective is to find out if EU trade preferences and regional trade agreements within SSA had increased trade flows. Estimating a gravity model augmented with measures of trade agreements, the paper made use of bilateral trade flows and key gravity covariates from CEPII database on 73 countries (48 SSA and 25 EU countries) over the period 1960-2006. After controlling for the endogeneity of the trade agreement dummy, accounting for multilateral price resistance and zero-valued trade flows, the findings indicate that the EU-ACP PTA and RTAs within ECOWAS and SADC have a positive and significant impact on bilateral trade involving SSA countries. In some cases the relative impact of the sub-regional RTAs was found to be stronger than the EU-ACP non-reciprocal PTA. The results therefore indicate the need for developing countries especially within SSA to focus on expanding and integrating regional markets in order to significantly improve trade performance.
https://www.econstor.eu/handle/10419/65446
Keywords: Bilateral Exports; Developing countries; Domestic Trade; Gravity Model; International Trade; Sub-Saharan Africa; Trade Costs

Using observable trade data to measure bilateral trade costs in sub-Saharan Africa - Turkson, Festus Ebo (CREDIT Research Paper, 2012)
Following closely the analytical approach adopted by Head and Mayer (2004) and Novy (2010), this paper derives a micro-founded bilateral trade cost measure for sub-Saharan Africa (SSA) as a function of observable domestic and inter-national trade data. The derived measure of trade cost by Novy (2010), consistent with the Ricardian and heterogeneous firm's models of trade, enables us to track changes in trade costs in SSA over time. This is a significant contribution to the trade cost literature in SSA because measures of many components of trade frictions in SSA have been unreliable. Based on bilateral trade data from BACI and production figures from the Trade, Production and Protection database by Nicita and Olarreaga (2007) for the period 1980-2003, our estimates of the tariff equivalent bilateral trade costs measure indicate that on average trade costs in SSA are relatively higher than other regions, confirming evidence which indicates trading costs in SSA to be the highest within the global trading system. The estimates indicate that SSA countries traded with each other at a lower cost than they did with other regions with the exception of the EU. Within SSA, member countries of economic blocs traded at relatively lower costs than trade with non-member countries. Using each of the main five economic blocs within SSA as a reference, overall average relative bilateral trade costs within bloc was significantly lower than across blocs. This paper therefore argues for increased efforts at regional integration within SSA to derive benefits from lower trade costs.
https://www.econstor.eu/handle/10419/65470
Keywords: Bilateral Exports; Gravity Model; Sub-Saharan Africa; Trade Costs

The Social Dimension of Regional Integration in ECOWAS - Robert, René (Social Science Research Network, 2004)
Regional economic integration arrangements have their own purpose, legal framework, institutional set-up, history, and trajectory, and this paper aims to study these factors in relation to the Economic Community of West African States (ECOWAS). When dealing with regional integration, it is important to consider governance, trade liberalization, and its social impact. The paper focuses on the West African Economic and Monetary Union (WAEMU) and the Organization for the Harmonization of Business Law in Africa (OHADA) to analyze labour law harmonization, poverty reduction strategies for development, gender empowerment, and democratic participation. Suggestions to strengthen socio-economic development include promoting social dialogue and how the International Labour Organization and other institutions' can help with better integration in Western Africa. Ultimately, identifying and understanding the unique economic integration arrangements of certain communities can help develop their paths towards a fairer globalization for all.
10.2139/ssrn.908485
Keywords: ECOWAS; Integration; Regional; Social dimension; WAEMU

Cooperation Without Enforcement? A comparative analysis of litigation and online reputation as quality assurance mechanisms - Bakos, Yannis; Dellarocas, Chrysanthos (Massachusetts Institute of Technology Sloan School of Management, 2003)
Online reputation mechanisms are emerging as a promising alternative to more established mechanisms for promoting trust and cooperative behavior, such as legally enforceable contracts. As information technology dramatically reduces the cost of accumulating, processing and disseminating consumer feedback, it is plausible to ask whether such mechanisms can provide an economically more efficient solution to a wide range of moral hazard settings where societies currently rely on the threat of litigation in order to induce cooperation. In this paper we compare online reputation to legal enforcement as institutional mechanisms in terms of their ability to induce cooperative behavior. Furthermore, we explore the impact of information technology on their relative economic efficiency. We find that although both mechanisms result in losses relative to the maximum possible social surplus, under certain conditions online reputation outperforms litigation in terms of maximizing the total surplus, and thus the resulting social welfar
Keywords: E-commerce; Game Theory; Information Technology; Internet; Litigation; Online Reputation Mechanisms; Quality Assurance